Concept of "awake venovenous extracorporeal membrane oxygenation" in pediatric patients awaiting lung transplantation. (11th October 2012) - Schmidt, F.; Sasse, M.; Boehne, M.; Mueller, C.; Bertram, H.; Kuehn, C.; Warnecke, G.; Ono, M.; Seidemann, K.; Jack, T.; Koeditz, H.
Abstract In patients awaiting LuTx, MV and ECMO are often the last ways to create a bridge to LuTx. Both interventions are associated with a poor posttransplant outcome and survival rate. To improve the results of these patients, new "bridging‐strategies" are necessary. Recent reports demonstrate promising results for the concept of "awake ECMO" in adult patients. To date, no data on this approach in pediatric patients have been available. We therefore describe the use of VV‐ECMO as a treatment strategy for RF in awake pediatric patients. It presents our experiences with the first three children treated using this new concept. Mean amount of time on ECMO was 44 days (range, 11.5–109 days). Two patients were successfully bridged to their LuTx. Both are still alive without any recurrences (24 and three months following LuTx). One patient died before a further LuTx after 109 days on ECMO due to adenoviral infection. Although reintubation was necessary in two patients, and total time being awake while on ECMO was <50%, we conclude that the concept of "awake VV‐ECMO" is feasible for the treatment of RF and can be used as a "bridging therapy" to LuTx.